Context‐dependent specialisation drives temporal dynamics in intra‐ and inter‐individual variation in foraging behaviour within a generalist bird population. Issue 8 (12th May 2021) - Baert, Jan M.; Stienen, Eric W. M.; Verbruggen, Frederick; Van de Weghe, Nico; Lens, Luc; Müller, Wendt
Abstract : Individual niche variation is common within animal populations, and has significant implications for a wide range of ecological and evolutionary processes. However, individual niche differences may also temporally vary as a result of behavioural plasticity. While it is well understood how niche variation is affected by changes in resource availability, comparatively little is known about the extent to which individual niche differences may vary within the annual cycle due to internal drivers. Here, we assess how time‐ and energy‐constraints imposed by incubating and brood rearing affect inter‐ and intra‐individual variation in the foraging behaviour of lesser black‐backed gulls, a generalist seabird with strong individual niche variation. To this end, we compared daily foraging trips of 22 breeding and 23 non‐breeding GPS‐tracked adult gulls from two colonies in the Southern Bight of the North Sea over the course of the breeding season. We find that breeding birds, unlike non‐breeding ones, did indeed alter their foraging behaviour during the breeding season. Both sexes reduced their searching effort by increasingly revisiting earlier foraging locations, allowing for shorter and more frequent foraging trips. Breeding females also showed pronounced shifts in their habitat use and strongly specialised on urbanised foraging habitats throughout the breeding season. Hence, while individual variation in habitat use remained largely consistent within non‐breeders and in breeding males, individual variation among breeding females almost completely disappeared. Female lesser black‐backed gulls are on average smaller, and therefore often outcompeted by males for the most profitable food sources. The temporal specialisation on spatially reliable anthropogenic food sources during breeding hence suggests a complex interplay between intrinsic competitive constraints, resource reliability and shifting time‐ and energy budges in shaping temporal dynamics in individual niche variation within our study population.